The PD-1 with PD-L1 Axis Is Pertinent with the Immune Modulation of Atrial Fibrillation by Regulating T Cell Excitation and Promoting the Secretion of Inflammatory Factors - Guodong Chang; Yingwei Chen; Zichang Liu; Yong Wang; Wenkun Ge; Yongan Kang; Shuling Guo (Journal of Immunology Research)
Objective. To analyze the role of PD-1/PD-L1 signaling pathway in regulating T cell activation and secretion of proinflammatory factors in atrial fibrillation. Methods. Forty-five patients with atrial fibrillation admitted to the cardiology department of our hospital from July 2019 to March 2021 were selected to be included in the atrial fibrillation group, and another 45 healthy volunteers were selected as the control group to compare the changes of T cell CD69 and human leukocyte antigen-DR (HLA-DR) expression in the peripheral blood of the two study groups; compare the changes of programmed death factor-1 on CD4+ and CD8+ lymphocytes in the peripheral blood of the two groups (PD-1) expression changes and PD-L1 and PD-L2 expression changes on peripheral blood myeloid dendritic cells (mDCs) cells; compare the changes of interleukin-2, interleukin-6, interleukin-10, and interleukin-17A (IL-2, IL-6, IL-10, and IL-17), tumor necrosis factor (TNF), and interferon gamma (IFN-γ) concentrations on peripheral blood inflammatory factors in the two groups; and isolate the two groups of peripheral blood mDCs cells; α interferon upregulated PD-L1 expression in the cells and analyzed the effect of PD-L1 expression on the ability of mDCs to stimulate T cells to secrete cytokines.Results. The positive expression rates of CD69 and HLA-DR on peripheral blood CD3+ T lymphocytes were significantly higher in patients in the atrial fibrillation group than in the control group, and the differences were statistically significant (P<0.01). The positive expression rate of PD-1 on CD4+ lymphocytes was significantly lower in patients in the atrial fibrillation group than in the control group (P<0.01). There was no statistically significant difference between the two groups in terms of PD-1 positive expression rate on CD8+ lymphocytes (P>0.05). The positive expression rate of PD-L1 on mDCs cells was significantly lower in patients in the atrial fibrillation group than in the control group (P<0.01), and there was no statistically significant difference between the two groups in the positive expression rate of PD-L2 on mDCs cells, PD-L1, and PD-L2 on CD4+ and CD8+ T cells (P>0.05). The concentrations of IL-2, IL-6, IL-10, and IFN-γ in peripheral blood were significantly higher in patients in the atrial fibrillation group than in the control group (P<0.05), and there was no statistically significant difference in the comparison of IL-17A and TNF concentrations in peripheral blood between the two groups (P>0.05). In the atrial fibrillation group, the ability of mDCs to stimulate T cells to secrete IL-2 and IFN-γ was significantly higher, and the ability to secrete IL-10 was significantly lower compared with the control group (P<0.05). After α interferon upregulated PD-L1 expression in cells, the ability of mDCs to stimulate T cells to secrete IL-2, IL-10, and IFN-γ cytokines was reversed in patients in the atrial fibrillation group, and the differences compared with the control group were not statistically significant (P>0.05). Conclusion. PD-1/PD-L1 signaling pathway may play an immunomodulatory role in the pathogenesis of atrial fibrillation by promoting increased secretion of inflammatory factors through regulating T cell activation.